Design and development of bubble-cap tray column for continuous transesterification plant in coconut-oil-based biodiesel production - GNANASELVI, P; SUBRAMANIAN, P (The Indian Journal of Agricultural Sciences, 2016)
A study was carried out on production of biodiesel from coconut oil using alkali catalyzed transesterification process by two different reactive distillation columns, viz. sieve tray and bubble-cap tray column. Coconut oil with free fatty acid content of 1.2% was used for transesterification. In laboratory scale batch system, among all the variations adopted, it was found that maximum methyl esters yield of 97.7% was obtained with 6:1 molar ratio of methanol-to-oil, 1% NaOH at 60ºC reaction temperature. A continuous flow transesterification using sieve tray reactive distillation column yielded 93.75% methyl ester with 5.55 min average reaction time at 65ºC under 4:1 molar ratio (methanol-to-oil). The excess alcohol was found to be 11.4 ml. Based on performance evaluation of sieve tray reactive distillation column, a new bubble-cap tray reactive distillation column was designed and developed for continuous biodiesel production. Maximum methyl ester yield was 96.2% with 5.55 min average reaction time at 65ºC under 4:1 molar ratio. Excess alcohol was found to be 17.1 ml. Daily average electricity consumption was found to be 13.6 kWh for continuous transesterification biodiesel production and processing cost was worked out as ` 26.03. Regression analysis was employed to evaluate the effects of molar ratio and temperature on the yield of methyl esters. The R2 value was 0.87 for sieve tray reactive distillation column and 0.92 for bubble-cap reactive distillation column which confirmed the validity of the predicted model. Based on the findings from the study, it was found out that continuous transesterification was more feasible and efficient way for production of biodiesel. It was concluded that bubble-cap tray reactive distillation column was found to be an effective than sieve tray column due to its increased yield (1 time), excess alcohol recovery (1.5 times) and better fuel properties.